2018
DOI: 10.1111/jerd.12373
|View full text |Cite
|
Sign up to set email alerts
|

Color difference thresholds for computer‐simulated human Gingiva

Abstract: The data on visual thresholds for healthy human gingiva can be used as quality control tool/guide for selection and evaluation of dental materials, interpretation of color-related findings in clinical dentistry and research, and for standardization in dentistry. It is of particular value that this study was designed based on in-vivo color evaluation of healthy keratinized gingiva of subjects of different ethnicities, age groups, and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
1
39
2
2
Order By: Relevance
“…Repeated evaluations leaving part of the data aside, guarantees the aforementioned performance on any new unseen gingiva data. None of the shade guide models provided CE lower than or equal to PTs for gingival color . However, achieving CE at or below PT is not a realistic goal or objective in dentistry.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Repeated evaluations leaving part of the data aside, guarantees the aforementioned performance on any new unseen gingiva data. None of the shade guide models provided CE lower than or equal to PTs for gingival color . However, achieving CE at or below PT is not a realistic goal or objective in dentistry.…”
Section: Discussionmentioning
confidence: 94%
“…Although an overall CE was not reported, the CEs were in all cases greater than AT for gingival color. Furthermore, the reported ME represented the extremely unacceptable color differences . A third study reported on color of healthy gingiva of a total of 362 subjects .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations